Automatic Portal Access Application Using Static Qr Code Reading - Suhartono Suhartono; Nurhani Nurhani; Satria Gunawan Zain (ULTIMATICS, 2022)
This study is a study that aims to determine the results of the automatic portal access application using a static QR Code reading based on the results of the ISO 25010 testing standard and to find out the results of using an automatic portal access application using a QR Code reading. The development model used in this research is the Rapid Application Development (RAD) model and the application quality test is based on the ISO 25010 quality standard. Data were collected using documentation and observation techniques. The instrument and system were validated by two system experts. Data were analyzed using descriptive statistical analysis techniques. Based on the test results using the ISO 25010 quality standard, the automatic parking application using QR Code reading has met the standards where: a) testing the functionality suitability aspect Testing the application is carried out by involving 2 (two) expert validators who are experienced in the field of application programming, the percentage is obtained in the category Very Good and has met the functionality suitability aspect; b) testing the performance efficiency aspect of the application can run well without experiencing a memory leak which results in a force close and launch fail so that the application is said to be successful and has met the performance efficiency aspect; c) Testing the maintainability aspect From the test results on the maintainability aspect, it shows that the maintainability aspect test has met three aspects of the test, including instrumentation, consistency, and simplicity, so the results of the maintainability aspect test can be said to meet the maintainability standard.